Factors impacting informed consent in cosmetic breast augmentation. (April 2023) - Whyte, Stephen; Bray, Laura; Brumpton, Martin; Chan, Ho Fai; Peltz, Tim S.; Tamar, Manisha; Dulleck, Uwe; Hutmacher, Dietmar W.
Abstract: Background: For women who undergo cosmetic breast augmentation, their post-operative risk assessment may not match their pre-operative understanding of the involved risks and likelihood of revision surgeries. This may be due to the potential issues surrounding whether patients are being fully informed about all possible risks and related financial implications during the consent phases of patient/doctor consultation. Methods: To explore comprehension, risk preference, and perceptions of breast augmentation procedure, we conducted a recorded online experiment with 178 women (18–40 years) who received varying amounts of risk-related information from two experienced breast surgeons in a hypothetical first consultation scenario. Results: We find patient's age, self-rated health, income, education level, and openness to experience to be significant factors impacting initial breast augmentation risk preferences (before receiving any risk information). Further, more emotionally stable patients perceived greater breast augmentation risks, were less likely to recommend breast augmentation, and were more likely to acknowledge the likelihood for future revision surgery. After providing women with risk-related information we find increases in risk assessment in all treatment conditions, and that increased amounts of risk information do decrease women's willingness to recommend breast augmentation. But that increased risk information does not appear to increase women's assessment of the likelihood of future revision surgery. Finally, we find some participant individual differences (such as education level, having children, conscientiousness and emotional stability ) appear to impact risk assessment post receiving risk information. Conclusion: Continuous improvement of the informed consent consultation process is vital to optimising patient outcomes efficiently and cost-effectively. Greater acknowledgement and emphasis on disclosure of related risks and financial burden when complications arise is also important. As such, future behavioural research is warranted into the factors impacting women's understanding both prior to and across the BA informed consent process. Highlights: There is potentially an issue surrounding whether patients are being fully informed in cosmetic augmentation. We find women's age, self-rated health, income, education & openness to experience, are all factors impacting preference. After providing women with risk information we find increases in risk assessment in all treatment conditions. Education, children, conscientiousness, and emotional stability appear to impact risk assessment post risk information provision.